Measurement of number concentrations and sizes of Au nano-particles spiked into soil by laser ablation single particle ICPMS. Issue 8 (17th July 2020) - Tuoriniemi, Jani; Holbrook, Timothy R.; Cornelis, Geert; Schmitt, Melanie; Stärk, Hans-Joachim; Wagner, Stephan
Abstract : A novel method to directly quantify nanoparticles (NPs) in a soil matrix by laser ablation single particle inductively coupled plasma mass spectrometry (LA-sp-ICPMS) was developed. Abstract : A novel method to directly quantify nanoparticles (NPs) in a soil matrix by laser ablation single particle inductively coupled plasma mass spectrometry (LA-sp-ICPMS) was developed. Different concentrations of 60, 100, or 250 nm diameter gold NPs (AuNP) were deposited directly on polyether sulfone (PES) ultrafiltration membranes or immersed in soil. The ICPMS sensitivity was calibrated using aqueous dissolved Au standards and an aqueous AuNP size standard dispersion was used to calculate the transmission efficiency. In the case of the soil samples, sizing proved to be more accurate when calibration occurred while ablating a non-spiked soil. A linear relation was found between the spiked AuNP number concentrations and the particle event frequencies measured in the ablated area. Particle recovery on PES filters ranged only between 29 to 42% and recovery of soil-spiked AuNP on thin tape was between 15 and 60% and increased with size. However, 70–85% mass recovery in the ablated area was obtained when the soil sample was deposited on a thicker, opaque double sided tape suggesting that the substrate material is instrumental in absorbing excess laser energy thus enhancing recovery. The rate of soil ablation and mass transfer into the plasma was quantified to calculate the recovery using the same soils spiked with indium. The presented method thus has significant potential to be used for routine quantification of the particle size distributions of engineered or natural NPs in soil and possibly other powder samples with significantly fewer artifacts than extraction followed by aqueous analysis.